IMPLEMENTASI SISTEM PEMASYARAKATAN DALAM RANGKA MEMBERIKAN PERLINDUNGAN HAK NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS III PAGARALAM - Abdullah, Alexander (Faculty of Law, University of Palembang, 2024)
Correctional Institutions, hereinafter referred to as Lapas, are institutions or places that carry out the function of Guidance for Prisoners. The existence of Correctional Institutions has regulations regarding the procedures for implementing guidance for Prisoners. Legal protection of prisoners' rights is based on Law Number 22 of 2022 concerning Corrections in realizing prisoner guidance. Fulfillment of prisoners' rights is supported by the provision of adequate facilities in order to realize the development of personality and independence of prisoners. Some of the obstacles faced by the Class III Pagaralam Correctional Institution in implementing the protection of prisoners' rights are the limited number of instructors who have special expertise, budget constraints in meeting the needs of providing consumption sometimes become obstacles if the number of prisoners exceeds the maximum capacity, over capacity which is an obstacle so that facilities and infrastructure are not optimal. It is hoped that the Class III Pagaralama Correctional Institution will continue to improve guidance and ensure the sustainability of the fulfillment of prisoners' rights, it is also hoped that through a restorative justice approach it can provide solutions to over capacity in correctional institutions, not only in the Pagaralam area but also in areas in Indonesia.